Communication and voting in heterogeneous committees: An experimental study - Quement, Mark T. Le; Marcin, Isabel (Journal of economic behavior & organization, 2020)
•We investigate communication in common value committees with heterogeneous preference types.•We study whether social preferences or cognitive constraints affect strategic communication.•Results are consistent with a model of cognitive heterogeneity.•The vast majority of naïve subjects consistently truth-tells and uses a decision heuristic.•Sophisticated subjects consistently lie and use their optimal decision-rule. We study experimentally the drivers of behavior in committees featuring publicly known diverse preference who engage in voting preceded by one shot cheap talk communication. On the aggregate, we find low lying levels and different preference types using decision rules biased towards the majority heuristic which consists in following the majority of announced signals. Our results are inconsistent with the predictions derived from the standard model as well as models of social preferences and homogeneous naive behavior. Results are instead consistent with the predictions of a model of cognitive heterogeneity, in which a large majority of unsophisticated subjects truth-tells and uses the majority decision heuristic, while a minority of sophisticated agents lies strategically and applies its payoff-maximizing decision rule, albeit with noise.